Managing information security - Vacca, John R. (Burlington, MA : Elsevier, 2010)
Managing Information Security offers focused coverage of how to protect mission critical systems, how to deploy security management systems, IT security, ID Management, intrusion detection and prevention systems, computer forensics, network forensics, firewalls, penetration testing, vulnerability assessment, and more. It offers in-depth coverage of the current technology and practice as it relates to information security management solutions. Individual chapters are authored by leading experts in the field and address the immediate and long term challenges in the authors$1 (Brespective areas of expertise.s
Information security essentials for IT managers: protecting mission-critical systems / Albert Caballero -- Security management systems / Joe Wright and James Harmening -- Information technology security management / Rahul Bhasker, Bhushan Kapoor -- Identity management / Jean-Marc Seigneur, Tewfiq El Maliki -- Intrusion prevention and detection systems / Christopher Day -- Computer forensics / Scott R. Ellis -- Network forensics / Yong Guan, Linfeng Zhang -- Firewalls / Errin W. Fulp -- Penetration testing / Jay Bavisi -- What is vulnerability assessment? / Almantas Kakareka.
Includes bibliographical references and index.
1
Keywords: Computer security -- Management; Computer networks -- Security measures; Penetration testing (Computer security)